Digitalisasi Manajemen Proyek melalui Project Managament Information System (PMIS) Berbasis Spreadsheet pada Program Pengabdian kepada Masyarakat di Perusahaan Konsultan Teknik: Indonesia - Saputra, Alexander; Maulana, Farrel Maisoon; Agustien, Salma; Permatasari, Intan; Puspita, Ika Arum (Jurnal Abdimas Madani dan Lestari (JAMALI), 2026)
This Community Service (Abdimas) program aims to enhance project management capabilities at PT Tritech Consult Indonesia through training and implementation of a Project Management Information System (PMIS) based on spreadsheets. As an engineering consulting company, PT Tritech Consult Indonesia manages various complex projects involving multiple resources and cross-functional coordination. However, project management has largely been conducted manually using conventional, non-integrated applications, resulting in limitations in data accuracy, information transparency, and the effectiveness of project monitoring and controlling processes. The solution offered in this program is training and mentoring on the implementation of a spreadsheet-based PMIS that is practical and easy to adopt. The PMIS is designed to support project scheduling, resource allocation, progress reporting, and structured, data-driven project monitoring. This approach is expected to improve operational efficiency, reduce the risk of project delays, and support faster and more accurate decision-making. The program was implemented through observation and interviews to identify partner needs, followed by the introduction of a PMIS dashboard and hands-on training for project management staff at PT Tritech Consult Indonesia. The training session was conducted on January 8, 2026, and received positive responses from participants. The program concluded with the formal handover of the PMIS dashboard as a commitment to the sustainability of system implementation. Overall, this community service activity had a positive impact on improving the effectiveness of the partner’s project management practices and has the potential to be replicated in similar consulting companies. This program is aligned with the Community Service Roadmap of the Enterprise and Industrial Management Systems (EIMS) Knowledge Group, particularly in the Digital Solution System focus area.